Application of Noise Attenuation on 2D Shallow Offshore Seismic Reflection Data: A Case Study from the Baltic Sea - Roshdy, E.; Mabrouk, W.; Metwally, A. (Engineering, Technology & Applied Science Research, 2022)
Noise is always present in offshore seismic data, as there isn't a single method that could eliminate all the forms of noise. In this study, noise removal techniques were applied to attenuate different noises in 2D shallow-marine seismic data from the Baltic Sea area. Amplitude recovery should be applied before the noise attenuation stage as a preconditioning process for showing all noises in the deeper part of the seismic data. Frequency filters (notch filter and low-cut filter), frequency-wavenumber (FK) filter, and swell noise attenuation (Deswell) were applied as robust noise attenuation techniques. The method of directly modifying the amplitude spectrum of the seismic data is known as frequency filtering. A notch filter can be used to remove the harmonic noise of the power line harmonic noise (mono-frequency noise). A low-cut filter can be used to remove the low-frequency noises due to the influence of hydrostatic pressure variations. The linearly correlated events, such as tail-buoy and operational noise, were removed using the FK filter. Incoherent noise, such as swell noise, can be attenuated by swell noise attenuation (Deswell). The seismic results are displayed before and after the applied noise attenuation techniques to prove the validity of the applied filters. This study aimed to show the importance of shallow offshore seismic data processing in removing different types of noise, as it increases the value of data for seismic data interpretation and marine geohazard assessment.